Fox in socks - Seuss, Dr. (New York : Beginner Books, 1993)
A collection of easy-to-read tongue twisters.
Elem. School Library Collection.
Library Journal.
School Library Media Quarterly (A.A.A.L.).
2.6.
2.6
K-3
Keywords: Nonsense verses; Tongue twisters; Nonsense verses; Tongue twisters; Nonsense verses; Tongue twisters; Readers (Elementary).